Poster 192: femoroacetabular impingement in elite skiers and snowboarders: return to sport and outcomes after hip arthroscopy - Waltz, R.; Comfort, S.; Philippon, M. (Orthopaedic Journal of Sports Medicine, 2022)
Objectives: Hip arthroscopy has been shown to be an effective treatment for femoroacetabular impingement (FAI) in high level athletes; however, limited outcomes and return to play data exists for hip arthroscopy in skiers and snowboarders. The purpose of this study is to determine the return to sport rate of elite skiers and snowboarders who have undergone hip arthroscopic surgery for FAI and to assess hip-related outcomes at a minimum 2-years follow up. Methods: Elite skiers and snowboarders who underwent hip arthroscopy for the treatment of FAI between 2005 and 2018 were identified through a retrospective review of prospectively collected data. Data was obtained from www.fis-ski.org, www.usskiandsnowboard.org, www.xgames.com, and www.wikipedia.org, including information on each players` career length, participation on a national team, and time between surgery and first competition post-surgery. Patient reported outcome measures (PROs) were prospectively collected pre-operatively and at minimum 2 years post-operatively. Results: Twenty-six elite skiers and snowboarders (34 hips) were included. The mean age at surgery was 24.5 ± 6.7 years (range 18.7-46.8). A total of 85% returned to elite level competition at 8.9 months (range 2.9-23.7) with an average career length of 3.6 ± 2.7 years. Four athletes required revision arthroscopy with adhesions being the most frequent indication. At mean follow-up of 7.7 ± 3.2 years, significant improvement in PROs was demonstrated for HOS-ADL (76 ± 20 to 95 ±6), HOS-SSS (63 ± 28 to 92 ± 14), mHHS (70 ± 19 to 89 ± 12), and SF12-PCS (45 ± 11 to 54 ± 8). Patient acceptable symptom state (PASS) was achieved in 88% for HOS-ADL, 88% for HOS-SSS, and 83% for mHHS. Median patient satisfaction was 10. Conclusions: The return to competition rate in elite skiers and snowboarders after hip arthroscopy for FAI is 85% at an average of 8.9 months with a career length of 3.6 years after surgery. Significant improvement in PROs was demonstrated for HOS-ADL, HOS-SSS, mHHS, and SF12-PCS with median patient satisfaction score of 10. These findings support hip arthroscopy as an effective procedure for the treatment of FAI in elite skiers and snowboards with symptomatic activity limiting hip pain allowing them to return to their previously level of competition at a high rate.